Flame retardancy of starch –based biocomposites — aluminum hydroxide-coconut fiber synergy - Gallo, E.; Sánchez-Olivares, G.; Schartel, B. (Polimery, 2013)
The use of coconut fiber (CF) agricultural waste was considered as an environmentally friendly and inexpensive alternative in flame retarded biocomposites. To decrease the high content of aluminum trihydrate (ATH) required, the thermal decomposition (thermogravimetry), flammability [oxygen index (LOI) and UL 94 test] and fire behavior (cone calorimeter) of a combination of CF and ATH were investigated in a commercial blend of thermoplastic starch (TPS) and cellulose derivatives. CF induced some charring activity, slightly decreasing the fire load and burning propensity in cone calorimeter test. ATH decomposes endothermically into water and inorganic residue. Significant fuel dilution as well as a pronounced residual protection layer reduces the fire hazards. Replacing a part of ATH with coconut fibers resulted in improved flame retardancy in terms of ignition, reaction to small flame, and flame-spread characteristics [heat release rate (HRR), fire growth rate (FIGRA), etc.]. The observed ATH and CF synergy opens the door to significant reduction of the ATH contents and thus to interesting flame retarded biocomposites.